Innovation and investments in a regional cross-sectoral growth model: A change is needed in European cohesion policies - Riccardo Cappellin (European Regional Science Association (ERSA), 2016)
This paper aims to indicate that an economic recovery of the European economy can be pulled by an increase of the aggregate demand and by the adoption of a new European cohesion policy having an industrial and a territorial dimension. The paper illustrates a theoretical model: the model of the 'cross-sectoral demand' and the 'cross-sectoral supply', where growth is based on the interdependent changes of the sectoral structure of the supply and the demand. A crucial role is attributed to the flows of new knowledge, innovation and investment, as factors which affect both the aggregate supply and the aggregate demand. The paper illustrates the characteristics of the equilibrium and the pattern of growth in the model of the 'cross-sectoral demand' and the 'cross-sectoral supply' and it compares this model with the traditional macroeconomic 'AD-AS model'. Then, it indicates that industrial and regional policies are complementary to the monetary and fiscal policies, as they may promote the creation of new productions and determine an increase of GDP and employment at the regional and national level, also in a short-medium term perspective and not only for long term development.
Keywords: E14; L52; O14; O18; O33; 330